Time-shift Management System - Lee, Gou Yao; Ab.aziz, Ruhaya (Applied Information Technology And Computer Science, 2022)
Woody House is a restaurant that is located in Kampar. The restaurant is still using Microsoft Excel in creating the work schedule. The problems that are facing by the restaurant included the work schedule created using Microsoft Excel is not effectively because of time consuming, caused wastage in company resources for assigning extra employees in certain shift and the employees may miss out the work schedule distributed in the Whatsapp group. The objectives of this project are to analyze and design a Time-shift Management System to replace the current scheduling method followed with developing and testing the proposed system. The target users are the manager and employees in restaurant. Prototyping model is applied in the project development. The proposed system will be designed as web-based system. The system will allow the users to register, login and manage users’ own account. The system will also allow the manager to manage employee, manage work schedule and generate a work schedule report while the employees should able to view and request change in the work schedule. The system will make announcement to users when change request is made or work schedule created. Lastly, the limitation of developed prototype will be refined in future.